DETEKSI Epistylis Sp. PADA UDANG VANAME (Litopenaues vannamei) DI DESA AKAR – AKAR KECAMATAN BAYAN KABUPATEN LOMBOK UTARA - Sri Rahayu Rizki; Candra Dwi Atma; Maratun Janah; Ni Luh Lasmi Purwanti (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2026)
This study aimed to detect the presence of the ectoparasite Epistylis sp. in Vaname shrimp (Litopenaeus vannamei) and to analyze its relationship with environmental quality in the culture systems of Akar – akar Village, Bayan District, North Lombok Regency. The research utilized a biopsy technique, collecting tissue samples from the carapace, gills, periopods, pleopods, and uropods. The results revealed that all 100 samples were infested with Epistylis sp., resulting in a prevalence rate of 100%. Water quality analysis showed a temperature of 32?, ammonia of 0,072 mg/L, nitrite of 0,049 mg/L, and orthophosphate of 2,110 mg/L. Notably, an extreme condition was observed in the dissolved oxygen (DO) level, which reached 0 mg/L. The pH value of 7,18 was slightly below the optimal range, while salinity remained stable at 24,7 ppt. In conclusion, the 100% infestation rate of Epistylis sp. Is closely associated with suboptimal water quality. Furthermore, high stocking density is considered a key contributing factor to the deterioration of the deterioration of the aquatic environment in this study area.